THE EFFECT OF FLIPPED CLASSROOM INTO FOCUS GROUP DISCUSSION IN SPEAKING SETTING CLASSROOM - Wahyuni, Resty; Ningsih, Widya Surya (Universitas Negeri Medan, 2024)
This study deals with the Effect of Flipped Classroom into Focus Group Discussion in Speaking Setting Classroom. The researcher took this method by expecting that students would be more active in communication and doing great speaking with their teacher and friends in learning English. This study was conducting by using experimental and control class and it took 68 (sixty eight) total students of SMAS Budi Agung Medan as sample. They were divided into two groups, they were 37 students were taken as experimental group and by the effect group discussion in speaking, 31 students were taken as control group by flipped classroom method-centre learning by teacher. The instrument of this study was making the sentences they could by paying attention the grammar, pronunciation, fluency, comprehension and vocabulary. The result of the t-test showed that the t-observed was higher than t-table (1.280>1.279). Group speaking method gave a significant effect on the students’ speaking. In order it is possible to make that the students' speaking enhanced as a result of the group discussion. The effect of speaking method in the students' flipped classroom performed better than the usual approach (TCL). Discussions in groups were of a lot of relaxing, cheerful, and challenging activities that make it difficult for students learn spoken English in the classroom.